4A.002 The impact of injury on insufficiently active women's participation in sport/physical activity. (14th March 2021) - Staley, Kiera; Donaldson, Alex; Mosler, Andrea; Bruder, Andrea; Seal, Emma; O'Halloran, Paul; Forsyth, Adrienne; Forsdike, Kirsty
Abstract : Background: Injury is a barrier to sport/physical activity (PA) participation, but the impact of this barrier for insufficiently active (not meeting minimum PA guidelines) women is unknown. Method: Insufficiently active women, who identified injury as a barrier to engagement in sport/PA, participated in an online concept mapping exercise. Results: Brainstorming (n=45) elicited 208 impacts of injury. After synthesis and editing, participants (n=25) sorted 94 impact statements into groups (mean no. of groups, 9.3; mode 6; range 4–15). Multidimensional scaling and hierarchical cluster analysis identified a nine-cluster solution listed from highest to lowest mean importance rating out of 5: Fear and frustration (17 statements;, importance 3.92); Physical implications of injury (15; 3.71); Activity restrictions (8; 3.66); Financial implications (4; 3.63); Worries (6; 3.46); Adjustment and management (14; 3.39); Mental and emotional wellbeing (14; 3.2); Impact on daily life (6; 3.03); and Social impact and engagement (10;2.82). Conclusion: The impact of injury extends beyond physical engagement in sport/PA. To increase PA in insufficiently active women who experience injury as a barrier, public/health professionals, governing sport bodies, insurance providers, and program deliverers need to be educated to understand the breadth of this barrier. Learning Outcomes: The impact of injury is multi-dimensional. Women who experience injury need access to evidence-based advice, affordable rehabilitation options, support (psychological/physical/logistical), and information about suitable sport/PA options. The program deliverer has an opportunity to provide information that will potentially reduce the impact of this barrier, see these women return to sport/PA earlier, and increase their levels of PA.